DEVELOPING A WORKSITE WELLNESS PROGRAM FOR THE SALINE COUNTY HEALTH DEPARTMENT TO BE USED AS A MODEL FOR OTHER RURAL CENTRAL KANSAS REGION - Perez, Daniel (My University, 2016)
This report covers projects and learning objectives conducted during a field experience for fulfillment of a Master in Public Health degree at Kansas State University. Research and projects were completed within the field experience timeframe. The field experience was completed at the Saline County Health Department (SCHD). SCHD is a county level health agency serving the residents of Salina and surrounding communities of about 55,000 individuals. The mission of SCHD is to assess community health status and available resources, develop policies to support and encourage better health, and to assure that necessary services are provided through other entities, by regulation or by direct provision of services. The primary objective for the field experience was to develop a work-site wellness program that could be used as a model for other central Kansas region counties which will meet the needs and desires of rural health department employees. Reducing the risk for chronic disease is a major objective for public health at every level. This concern also applies to public health employees. How work-site wellness programs can be developed to reduce chronic disease risk in rural communities is not well understood. Many of the studies pertaining to work-site wellness programs at health departments are conducted in urban areas with large staff groups (Davis, et al., 2009; Perez, Phillips, Cornell, Mays, & Adams, 2011.) One size does not fit all when it comes to work-site wellness programs as there are large variations in needs and available resources. Health disparities between rural and urban populations are on the rise (Singh & Siahpush, 2014) and public health employees living in rural areas are no exception. This is why we must provide resources and programs such as work-site wellness programs to rural and urban public health employees alike. Detailed results from qualitative surveys and interviews held with SCHD staff were provided in this report. Some of the barriers to wellness for the worksite were lack of resources, human capital, and inadequate facilities such as lack of showers and exercise equipment. Some of the facilitators for the work-site wellness program were that the majority of SCHD staff were interested and were planning or already making positive health behavior changes.
Keywords: Salina County Kansas; Chronic disease